2022
DOI: 10.11005/jbm.2022.29.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Signal-Regulated Kinase Mitogen-Activated Protein Kinase Pathway in Osteoblasts

Abstract: Extracellular signal-regulated kinases (ERKs) are evolutionarily ancient signal transducers of the mitogen-activated protein kinase (MAPK) family that have long been linked to the regulation of osteoblast differentiation and bone formation. Here, we review the physiological functions, biochemistry, upstream activators, and downstream substrates of the ERK pathway. ERK is activated in skeletal progenitors and regulates osteoblast differentiation and skeletal mineralization, with ERK serving as a key regulator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 119 publications
(138 reference statements)
2
6
0
Order By: Relevance
“…The MAPK signaling pathway mediates various physiological processes, including cell growth, development, proliferation, differentiation, aging, and death. Studies have shown that the MAPK signaling pathway promotes osteoblast proliferation, differentiation, and delayed apoptosis through various pathways ( Luo et al, 2005 ; Greenblatt et al, 2022 ). In the NRFM-Zr group, there were 7 genes involved in this pathway, while the MTA group had 4 genes ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway mediates various physiological processes, including cell growth, development, proliferation, differentiation, aging, and death. Studies have shown that the MAPK signaling pathway promotes osteoblast proliferation, differentiation, and delayed apoptosis through various pathways ( Luo et al, 2005 ; Greenblatt et al, 2022 ). In the NRFM-Zr group, there were 7 genes involved in this pathway, while the MTA group had 4 genes ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of load-induced bone formation, the integrin-based adhesion complex holds significant importance and is ubiquitously expressed across all types of bone cells [ 41 , 42 ]. However, since integrins lack inherent enzymatic activity, the transmission of signals through focal adhesion hinges upon associated molecules that trigger downstream signaling events such as intracellular calcium release, tyrosine kinase and MAP kinase activation [ 43 , 44 ]. The Focal adhesion kinase (FAK) family, comprising of FAK and proline-rich tyrosine kinase 2 (PYK2), represents significant tyrosine kinases activated upon integrin engagement, responsible for the regulation of osteoclast adhesion and bone resorption [ 45 ].…”
Section: Molecular Effectors and Mechanisms Involved In Exercise-rela...mentioning
confidence: 99%
“… 92 , 93 , 94 Another relevant substrate of ERK that is associated with osteoblast formation is the Fos family of subunits of the AP-1 transcriptional complex, comprising FOS, FOSL1, FOSL2, and FOSB. 95 The mechanism of Fos and AP-1 stimulation in osteoblast formation by ERK activation remains unclear; however, FOS proteins via cGMP-mediated ERK are reportedly involved in bone formation by mechanical stimulation. 95 , 96 …”
Section: Signalling Pathways In Bone Regenerationmentioning
confidence: 99%
“… 95 The mechanism of Fos and AP-1 stimulation in osteoblast formation by ERK activation remains unclear; however, FOS proteins via cGMP-mediated ERK are reportedly involved in bone formation by mechanical stimulation. 95 , 96 …”
Section: Signalling Pathways In Bone Regenerationmentioning
confidence: 99%